Teachers' Perception of Online Teaching and Factors Influencing Intention to Use Online Platforms during COVID-19 (Prithvi Academic Journal, 2022)
Since the outbreak of COVID-19 and the sudden closure of all educational institutions, teachers have been forced to adapt to online teaching through various online platforms as the only feasible option. In this regard, the study investigates the factors and perceptions that influence teachers’ intention to use online classroom applications in teaching online. Using the descriptive cross-sectional online survey of 227 teachers teaching online during the pandemic, the findings revealed a positive perception of teaching online using online platforms. Further, the study results found that training and administrative support, trust, digital literacy, online teaching ability and perceived security are the major factors affecting the intention to use online classroom applications. These factors have a favorable influence on the choice to use. The study results have some practical implications and limitations of the study have been discussed, which are potential future research areas.